Evaluasi Peranan Teknikal Dan Manajerial Guru Dalam Implementasi E-Raport (Raport K13) pada SMA Negeri Kota Pagar Alam - duince fernande; Widya Cholil; Linda Atika (Jurnal Teknologi Informasi Mura, 2019)
There are still many shortcomings in the implementation of the 2013 curriculum from the high school level, firstly the problem of assessment is considered complicated because the assessment covers four aspects of assessment, spiritual attitude, social attitude, knowledge, and skills. This study aims to evaluate and identify technical and managerial abilities in the implementation of K13 report cards at the Pagar Alam Municipal High School by using the UTAUT and EUCS approaches